Using Certainty Factor Method To Determine Work Commitment Generation Y - Syahrul Fahri; Hasanul Fahmi; Jijon Raphita Sagala; Yuda Perwira; Yessy F A Lubis; Nurjamiyah Nurjamiyah; Mufida Khairani (Universitas Bina Sarana Informatika, 2021)
At present, in the world of work there are three generations that color the workforce, namely baby boomers born in 1943-1960, generation X 1961-1979 and generation Y 1980-1994. Generation Y is an individual born in the development of information technology and a high level of education so that Generation Y is very achievement-oriented, hard-working and will strive to achieve success but Generation Y has a tendency to move around at work, lack of work commitment so that this causes companies to experience difficulties in determining the performance commitment of generation Y if this continues it will have an impact on the sustainability of a company, so we need a certainty factor method to determine the work commitment of generation Y. from research that has been done by taking one sample by applying the certainty factor method produced that one of the Y generation has a commitment to the feeling of love in an organization that raises the willingness to stay and foster social relationships and appreciate the value of relationships with the organization because it has become a member or ganisasi (Affective commitment)